Functional connectivity alterations in patients with chronic hepatitis C virus infection: A multimodal MRI study. Issue 3 (4th November 2016) - Kharabian Masouleh, S.; Herzig, S.; Klose, L.; Roggenhofer, E.; Tenckhoff, H.; Kaiser, T.; Thöne‐Otto, A.; Wiese, M.; Berg, T.; Schroeter, M. L.; Margulies, D. S.; Villringer, A.
Summary: Chronic hepatitis C virus (HCV) infection is associated with fatigue and depression. Cognitive impairments are also reported in a smaller number of HCV‐positive patients. Recent studies linked HCV to low‐grade inflammation in brain. Here, we test the hypothesis that chronic HCV is associated with 3T‐neuroimaging‐derived grey matter volume (GMV) and functional connectivity alterations in a sample of chronic HCV (1b), without severe liver disease. Regional GMV and resting‐state fMRI‐derived eigenvector centrality (EC) were compared between 19 HCV‐positive patients and 23 healthy controls (all females, 50‐69 and 52‐64 years, respectively), controlling for white matter hyperintensities and age. Standard tests were used to assess fatigue, depression and cognitive performance. Also, liver fibrosis stage and viral load were quantified among patients. In comparison with controls, HCV‐positive patients had higher scores in fatigue and depression, and worse alertness scores. The groups performed similarly in other cognitive domains. We report higher EC in a cluster in the right anterior superior parietal lobule in patients, while no differences are found in GMV. Post hoc functional connectivity analysis showed increased connectivity of this cluster with primary and secondary somatosensory cortex, and temporal and occipital lobes in patients. Higher mean EC in the superior parietal cluster, adjusted for mean framewise displacement, was associated with better memory and attention performance, but not with fatigue, depression, viral load or level of liver fibrosis, among patients. These results suggest a compensatory mechanism in chronic hepatitis C and explain equivocal results in the literature about cognitive deficits in infected persons. Further studies should define the relation of these connectivity changes to the brain's inflammatory activity.